Fully 3D-Printed Miniature Soft Hydraulic Actuators with Shape Memory Effect for Morphing and Manipulation - Qing, Haitao (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.